Performance of an internally cooled and heated desiccant-coated heat and mass exchanger: Effectiveness criteria and design methodology. (April 2021) - Jagirdar, Mrinal; Lee, Poh Seng; Padding, Johan T.
Highlights: Effectiveness of a close-to-ideal HMX approaches 1, based on the novel definition. A simple psychrometric-chart based method can well predict the ideal performance. New design methodology predicts dehumidification performance to within ±1.1 g/kg d.a. Well-designed real HMX can manage complete latent heat load using waste heat at 50 °C. HMX with large depth and small fin pitch has high effectiveness. Abstract: Internally cooled and heated desiccant-coated heat and mass exchangers (ICHDHMX) driven by low-grade heat are very attractive owing to their energy-saving potential, especially for applications where substantial moisture removal (such as air-conditioning) is a necessity. In this paper, we derive equations for the performance of an ideal ICHDHMX, allowing us to define humidity-ratio effectiveness ( εY ) and relative-humidity effectiveness ( εRH ) such that their values approach 1 as the performance approaches that of an ideal ICHDHMX. Besides an equation-based approach, an easy-to-use psychrometric-chart based approach is presented to determine the performance of an ideal ICHDHMX. We invoke conservation principles to ascertain whether or not it is feasible to use the ICHDHMX for a given set of inlet conditions of air and water streams for dehumidification and regeneration. The dimensions of the ICHDHMX can be determined using this methodology, not even requiring knowledge of a tuning parameter unless a precise outlet specific humidity is required. Simulations are conducted for cases involving three incoming hot water temperatures (38, 44 and 50 °C) and several mixing ratios of room return air (25 °C at 0.011 kg/kg dry air) and outdoor air (32 °C at 0.02 kg/kg dry air), typical of warm and humid weather conditions. For all cases, the cool-water inlet is fixed at 30 °C. The results show that even when the dehumidification air-stream humidity is high, if the regeneration air-stream humidity is low (typical of room-exhaust air), the operation of an ICHDHMX is feasible using a low regeneration temperature of only 38 °C. When the regeneration temperature is 50 °C, the exchanger can operate under the complete range of humidity conditions tested. A cooling coefficient of performance up to 9.8 and effectiveness value up to 0.88 is realized, while the fluid power required is generally very low. These findings substantiate the case for commercial adoption of this technology for air-conditioning.